Mathematics in the disciplines at the transition to university - McAlinden, Mary; Noyes, Andrew (Oxford University Press, 2018)
Mathematics education is highly valued in advanced economies due to its role in developing skilled workforces, economic resilience and social wellbeing. However, university academics across disciplines regularly bemoan undergraduate students’ under-preparedness for the mathematical and quantitative demands of undergraduate degree programmes. In this paper we consider this issue. We begin with a research synthesis of relevant literatures on mathematics within university study in the natural sciences (physics, chemistry and biology) and social sciences (economics, geography, psychology) that highlights the international nature of this problem. We then develop an historical national case study of how mathematics for pre-university study in England has evolved, culminating in a recent policy move which mandates the assessment of mathematics within disciplines. Finally, by integrating these two distinct perspectives we discuss wider issues relating to mathematics for the transition to higher education.